Gender Differentials in Labour Allocation in Farming Systems of Jharkhand - V. Lakra; R. Sinha; C. Kerketta (Journal of Agricultural Extension Management, 2025)
Jharkhand, a newly created state in eastern India is primarily an agricultural region where 71 % of the population depends on agriculture (Singh 2002). The economy depends on subsistence agricultural practices mostly in rainfed conditions. Majority of the farmers belong to small and marginal farmers group. Farm women play a significant role in agriculture and have a major share of the responsibility for enhancing production, productivity and sustainability. They play a vital role at every step of agricultural activities. Despite their significant participation in farming, they are not being involved in the mainstream of development. Keeping these facts in view, the study was conducted with the objectives of understanding. To study the socio-economic characteristics of the farmers and gender differentials in Labour allocation